SUPPORTING AFRICAN DIGITAL LIBRARY PROJECTS: EXPERIENCES FROM THE FIELD - Kujenga, A.; de Vries., R. (My University, 2012)
This paper outlines the activities of the African Digital Library Support Network (ADLSN) in enhancing knowledge access by promoting and assisting the development of low-cost digital libraries in Africa. It aims to stimulate practical discussion on how digital library projects can be run in Africa in a collaborative way. It focuses on the milestones and challenges of the ADLSN, starting by narrating events leading to the formation of the network, its structure and its strategic directions. The notion of National Centres through which the Network grew is discussed and the financing of activities is addressed. The paper examines some of the barriers that must be taken into account when developing digital libraries and also makes recommendations for policies related to collaborative national and/or regional digital library projects. The paper uses a qualitative approach and is based on the personal experiences and observations of the authors together with some informal interviews and document analysis.
Keywords: SUPPORTING AFRICAN DIGITAL LIBRARY PROJECTS: EXPERIENCES FROM THE FIELD